Study on the correlation of the TLR4/MyD88 axis with the degree of inflammatory response in patients with synovitis of the knee joint: Association of TLR4/MyD88 with knee synovitis - Yang, Yanyan; Lu, Xia; Sun, Xiaoli; Li, Min; Mierzhati, Ayinigeer; Li, Huazhang (Cellular and Molecular Biology, 2023)
This work aims to provide a novel reference for future diagnosis and treatment of synovitis of the knee joint (SKJ) by analyzing the correlation of the TLR4/MyD88 axis with the degree of inflammatory response in SKJ patients. First, this study retrospectively analyzed the clinical data of 46 SKJ patients (research group, RG) treated in our hospital from January 2021 to December 2022 and 52 concurrent healthy controls (control group, CG). Concentrations of TLR4, MyD88 and inflammatory factors (IFs) in peripheral blood were measured, and differences in TLR4 and MyD88 between groups were observed to explore the diagnostic performance of the two for SKJ. Additionally, the correlation of TLR4 and MyD88 with IFs and Western Ontario Mac Master (WOMAC) scores in SKJ patients was discussed. Through the above experiment, we found that TLR4 and MyD88 presented higher mRNA levels in RG than in CG (P<0.05), both of which had excellent diagnostic efficiency for SKJ. Pearson correlation coefficients identified a positive correlation of TLR4 and MyD88 mRNA with IFs and WOMAC scores (P<0.05). Therefore, The TLR4/MyD88 axis is activated in SKJ patients and is strongly related to the intensification of inflammatory responses.